1988
DOI: 10.1295/polymj.20.1021
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on the Radical Copolymerization of N-Methyl- and N,N-Dimethylacrylamides and N-Methylmethacrylamide with Methyl Methacrylate

Abstract: ABSTRACT:Solvent effect on radical copolymerizations of N-methylacrylamide (AA) and Nmethylmethacrylamide (MA) with methyl methacrylate (MMA, M2) was studied using benzene (BZ), dioxane (DO), acetonitrile (ACN), ethanol (EtOH), and N,N-dimethylformamide (DMF). Spectroscopic studies revealed that the solvents influence these amide monomers (M1) with regards to their association by hydrogen-bonding and dipole-dipole interaction. The solvent ability which makes the self-associations of AA and MA more effective de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Poly(DMA‐ co ‐BMA) and poly(AMO‐ co ‐BMA) were polymerized with more than 80% monomer conversion in the current investigation. The composition of the copolymers could be controlled by the monomer ratio in the reaction solution 18. In the polymerization of poly(VP‐ co ‐BMA), it was slightly difficult to obtain high VP monomer conversion, and so it was polymerized under longer reaction times than the other copolymers in this investigation 19…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Poly(DMA‐ co ‐BMA) and poly(AMO‐ co ‐BMA) were polymerized with more than 80% monomer conversion in the current investigation. The composition of the copolymers could be controlled by the monomer ratio in the reaction solution 18. In the polymerization of poly(VP‐ co ‐BMA), it was slightly difficult to obtain high VP monomer conversion, and so it was polymerized under longer reaction times than the other copolymers in this investigation 19…”
Section: Resultsmentioning
confidence: 95%
“…Each of the hydrophilic monomers N,NЈ-dimethylacrylamide (DMA), N-acryloylmorpholine (AMO), and N-vinylpyrrolidone (VP) was polymerized with the hydrophobic monomer n-butylmethacrylate (BMA). Using AIBN (2.0 ϫ 10 Ϫ2 mol/L) as a free radical initiator, copolymerization was carried out in DMF at 60°C under N 2 for 4 -7 h. 18,19 The monomer concentration was 1.0 mol/L and the total volume of solution was 300 mL. The reaction mixture was subsequently poured into a large excess of diethyl ether.…”
Section: Copolymerization Of Amphiphilic Copolymersmentioning
confidence: 99%
“…That is, the propagating chain end easily interacts with polar solvent resulting in lower kp. IR studies on monomer solvent mixture also showed the interaction between polar groups (NH) of monomer and various solvents 15 (Table I). The lower the frequency of absorption is, the stronger the interaction was obtained.…”
Section: Scheme 4 Synthesis Of Pumai/rmentioning
confidence: 93%
“…Solvent may change the monomer reactivity ratio and monomer association during the polymerization process and thus influence the molecular weight/intrinsic viscosity of the polymer [4,5]. Different solvents like ethyl acetate (PEA1), acetone (PEA2) and methanol (PEA3) were used to study the effect of solvent on the intrinsic viscosity of the polymer.…”
Section: Optimization Of Reaction Conditions For Polymer (Pea) Synthesismentioning
confidence: 99%